Islam as a Discursive Tradition: A Study of Traditional Islamic Boarding School Kiais’ Perspectives in Banten on Responding to Fidyah and Uang Shalawat Traditions - Fahmi, Zulkifli Reza; Hudaeri, Mohamad (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2025)
Traditional Islamic boarding schools in Banten play a central role in maintaining and developing Islamic traditions that adapt to local culture. Kiai as the leader of the Islamic boarding school not only maintains the purity of Islamic teachings but also acts as a mediator between religious values and community traditions. This study examines the response of traditional Islamic boarding school kiai in Banten to two local traditions, namely fidyah and sholawat money, using a qualitative descriptive approach and case study. This study found that the fidyah tradition in Banten has unique characteristics, such as the use of gold as a substitute for rice and the permissibility of borrowing to pay for it. Kiai provide legitimacy based on classical books such as I'anatu-t-thalibin and Nihayatu-z-zain, and also adapt their practices to social realities. Meanwhile, the tradition of sholawat money given to the congregation of the funeral prayer is seen as a form of charity and social respect. Kiai refer to the hadith about the virtue of congregational prayer and the recommendation to give charity to legitimize this practice. These two traditions demonstrate the dynamics of Islam as a living discursive tradition that continues to adapt without losing its authenticity. Kiai act as cultural brokers who connect religious texts with community practices, ensuring that traditions remain relevant and meaningful. This study contributes to understanding the role of pesantren and kiai in maintaining harmony between religion and local culture in Banten